Dynamics of clinical changes in patients with kerato-conjunctivitis influenced by thiol drugs (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Kerato-conjunctivitis is a severe pathology, so search for the new ways and methods of treatment of this disease is still one of the urgent problems of ophthalmologyMaterials and Methods: There were examined 95patients. The first group (con¬trol) included 45 patients with kerato-conjunctivitis treated only with conventional therapy. The second group (basic) — 50patients with kerato-conjunctivitis who received thiol drugs in addition to the primary therapy.Results: While analysing the results of treatment, severity of corneal edema during the first observation period was reduced by 32 %, in the second period — 42 %, in the third period — 30 %. Intensity of inflammatory infiltration in the first observation period was reduced by 23 %, in the second period — 42 %, in the third — 25 %. Intensity of corneal staining with fluorescein in the study group after treatment during the first observation was reduced by 10 %, in the second period — 20 %, in the third — 18 % compared with the control group.Conclusion: The results of clinical studies indicate that the inclusion of thiol drugs in the complex treatment of patients with kerato conjunctivitis significantly reduces the severity of clinical symptoms and allows to stop the disease process in the cornea in shorter time.
Keywords: keratitis; conjunctivitis; thiol drugs